A Ukrainian multicenter prospective study of the value of PET/ CT prognostic role in primary patients with Hodgkins lymphoma in a real-life cohort - Novosad, Olga; Skrypets, Tetiana; Pastushenko, Ian; Kadnikova, Tetiana; Gorbach, Oleksandr; Kozlov, Viktor; Mykhalska, Larisa; Kosinova, Viktoria; Kostiukova, Nina; Karnabeda, Oksana; Stratienko, Viktoria; Novikov, Mykola; et al. (Klinicka onkologie, 2020)
INTRODUCTION: In recent years, the positron emission tomography combined with computed tomography (PET/CT) has changed and the treatment approaches in Hodgkins lymphoma (HL) patients have entirely improved. The main idea in several studies is the use of PET/CT and the International Prognostic Score (IPS) protocols in identification of patients within a high-risk group and potential early relapse/refractory disease. MATERIALS AND METHODS: This study was based on PET/CT evaluation and treatment strategies of patients from eight Centers of Hematology in Ukraine. The patients included were newly dia-gnosed with HL and were aged 67 years or younger. They received a treatment with ABVD or BEACOPP-14/esc or “switched-regimens” (ABVD + BEACOPP-esc/14, BEACOPP-esc/14 + ABVD). The primary endpoints were to assess a correlation between PET/CT findings at the time of dia-gnosis, response to the therapy and clinical outcome (relapse/death) for patients with early and advanced stages of HL. The secondary endpoints were to evaluate the relationship between IPS and PET/CT findings. RESULTS: The study group included 106 patients. The overall response rate (ORR) was 90.5%. The ORR for patients with stages I-II was 96.5% (55/57) vs. 91% (41/45) for stage III-IV patients. In total, the disease progression occurred in 58.3% (7/12) of PET2+ patients and in 13.3% (12/90) of PET2 patients (P < 0.05). No significant difference was found between the event free survival (EFS) rate and IPS for patients with PET2+ vs. PET2, (log-rank test; P = 0.4). The PET3 status was found in 88.8% (79/89) of the study group patients and 1.2% (10/89) had a PET3+ status (P < 0.05). Using the Cox regression, we confirmed a significant correlation between EFS with PET3 Deauville scale (DS) and IPS. Patients with DS 1-2, DS 3 and DS 4-5 had a 1-year event-free survival of 94.4%, 100% and 33%, respectively (HR 0.56; 95% CI 1.07-2.8; P < 0.02). Our multivariable analysis showed no statistically significant correlation between PET2+ and PET3+ status and extranodal involvement or large tumor burden. CONCLUSION: The results of using PET/CT in patients with primary HL demonstrated a high prognostic value of PET at the end of the treatment. In addition, we confirmed the predictive role of IPS prognostic model in the treatment outcome depending on PET status.
Keywords: senioři; analýza přežití; prokarbazin; bleomycin; Doxorubicin; dakarbazin; cyklofosfamid; prednison; Male; Ukrajina; Survival Analysis; Prognosis; mladiství; Hodgkin’s lymphoma – positron emission tomography – prognosis – survival; Middle Aged; mužské pohlaví; Prospective Studies; Adult; mladý dospělý; Hodgkin Disease; Bleomycin; Ukraine; Vincristine; Positron Emission Tomography Computed Tomography; Young Adult; doxorubicin; ženské pohlaví; prognóza; Cyclophosphamide; Humans; prospektivní studie; Procarbazine; Prednisone; Dacarbazine; Etoposide; PET/CT; lidé středního věku; etoposid; vinkristin; Antineoplastic Combined Chemotherapy Protocols; Hodgkinova nemoc; protokoly protinádorové kombinované chemoterapie; Vinblastine; dospělí; Female; Aged; Adolescent; lidé; vinblastin